Crosstalk Between PD-1/PD-L1 Blockade and Its Combinatorial Therapies in Tumor Immune Microenvironment: A Focus on HNSCC - Lin, Weimin; Chen, Miao; Hong, Le; Zhao, Hang; Chen, Qianming (Frontiers in Oncology, 2018)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide with a poor prognosis and high mortality. More than two-thirds of HNSCC patients still have no effective control of clinical progression, and the five-year survival rate is less than 50%. Moreover, patients with platinum-refractory HNSCC have a median survival of less than six months. The significant toxicity and low survival rates of current treatment strategies highlight the necessity for new treatment modalities. Recently, a large number of studies have demonstrated that programmed cell death protein-1 (PD-1) and its ligand, programmed cell death protein ligand-1 (PD-L1) play an essential role in tumor initiation and progression. PD-1/PD-L1 blockade has shown a desired and long-lasting therapeutic effect in the treatment of HNSCC and other malignancies. However, only a small number of patients with HNSCC can benefit from PD-1/PD-L1 blockade monotherapy, while the majority of patients do not respond. To overcome the unsatisfactory therapeutic effect of PD-1/PD-L1 blockade monotherapy, combining other treatment options for HNSCC (including chemotherapy, radiotherapy, targeted therapy, and immunotherapy) in the treatment scheme has become a commonly used strategy. Herein, the potential mechanisms underlying the crosstalk between PD-1/PD-L1 blockade and its combinatorial therapies for HNSCC were reviewed, and it is hoped that the improved understanding of the crosstalk process would provide further ideas for the design of a combinatorial regimen with a higher efficiency and response rate for the treatment of HNSCC and other malignancies.